Investigating the Relationship between Resident Physician Implicit Bias and Language Use during a Clinical Encounter with Hispanic Patients. Issue 1 (2nd January 2023) - Wolsiefer, Katherine J.; Mehl, Matthias; Moskowitz, Gordon B.; Cagno, Colleen K.; Zestcott, Colin A.; Tejeda-Padron, Alma; Stone, Jeff
ABSTRACT: Prior research suggests that the implicit biases of physicians are negatively associated with quality of medical care and patient satisfaction among minority patients. However, relatively little is known about how physicians express these subtle forms of bias in patient interactions. This study examined the implicit and explicit anti-Hispanic biases of 53 resident physicians and the relationship between anti-Hispanic bias and language use during outpatient medical appointments with 291 Hispanic patients. Physician implicit bias was positively associated with use of interrogatives and work-related words and negatively associated with the use of prepositions and relativity-related words (e.g., words related to time and the future). These findings contribute to the growing body of evidence suggesting that, in addition to nonverbal and paraverbal behaviors, providers may communicate implicit bias to patients through the words they use during a clinical visit.